Perlindungan Hukum terhadap Anak di Era Globalisasi Antara Ide dan Realita - Layyin Mahfiana (Justicia Islamica, 2013)
Globalization is an inevitable development of the world. Every citizen must be ready to face this era of globalization as well as children. There are many positive aspects that can be utilized by children to support their growth and learning, but there are also many negative aspects that must be watched out for. The rule of law regarding child protection in this era of globalization has been established, therefore its law enforcement requires the role of parents, society, schools, government to create a proper environment for the development of children's souls.